(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
This research study takes a look at the juvenile justice system and compares and contrasts the two approaches of punishment and rehabilitation. This country’s system for dealing with young offenders has evolved significantly throughout the years, with a growing focus on rehabilitation rather than punishment for youth offenders. In this examination of research, statistics, and case studies, we look at how rehabilitation programs affect recidivism, long-term outcomes, and the rehabilitation of juvenile offenders. Furthermore, it evaluates the possible negative effects of punitive measures on juvenile offenders, such as making their criminal conduct worse and limiting their opportunities for the future. This research aims to contribute to the ongoing conversation on effective strategies for dealing with juvenile offenders.